The necessary remodeling of social services in the aging society - Pérez Gázquez, Isabel M. (Street Art & Urban Creativity, 2025)
The increase of dependency linked to population aging represents a great challenge for public authorities, which must guarantee the well-being of citizens through the necessary benefits. Objective: analyze the state of the support system for autonomy and dependency and determine if it is evolving in line with the increase in care needs linked to population aging. Methodology: study of regulations and data associated with population aging, dependency benefits and care centers that make up the system. Results: network of healthcare services is evolving in line with the increase in needs linked to population aging. Conclusions: public authorities must take measures and increase this network of services, with creation of new centers and/or alternatives for community care such as robotic housing, collective housing, co-location, cooperatives, etc.